Nilai Ekonomi Lahan Pertanian di Wilayah Kerja Cabang Dinas Kehutanan IV Kabupaten Cianjur Jawa Barat - Miftakhul Arifah; Andjar Astuti; Aris Supriyo; Sulaeni Sulaeni (JURNAL AGRIBISNIS TERPADU, 2023)
Land is the most important resource in supporting agricultural activities but land is limited. Therefore, land use must be wise and need economic considerations. The economic value of agricultural land is seen based on the level of fertility which is quantified by the production and production costs. This study aims to determine the average economic value of agricultural land and determine the most optimum economic value of land based on the types of commodities in Forestry Service Branch IV Working Area, Cianjur Regency, West Java. This research was conducted in Cianjur Regency, West Java from November 2022 to May 2023. Data was collected through direct interviews with 40 respondents. The average economic value of agricultural land in Forestry Service Branch IV Working Area, Cianjur Regency, West Java is Rp. 8.130/m²/cycle. The most optimal economic value of land in one cycle is the chili commodity in the amount of Rp. 9.530/m²/cycle while the most optimum economic value of land in one year is the cabbage commodity of Rp. 28.218/m²/year.